(untitled) (Terr@ Plural, 2023)
This work seeks to contextualize, apprehend and quantify the process of expansion of postgraduate programs in Geography in Brazil in the last three decades, that is, between 1991 and 2020. For this purpose, the policies for the implementation, consolidation and expansion of postgraduate studies in the country are discussed in general terms since the 1960s, before carrying out a historical review of teaching and research in Geography and examining the dilemmas and challenges of dissemination of its master’s and doctoral programs since the second half of the 20th century. Finally, it was proceeded to the quantification and geographic characterization of this expansion since 1991, a period when there was a remarkable growth in the number of programs both in regions where they already existed and in new spatial contexts. In addition to quantitative expansion, there was a deconcentration that resulted in the reversal of the initial situation of extreme concentration of programs in the Southeast, specifically in São Paulo State. If in 1991 only six states concentrated the ten existing programs, half of which were in that state, in 2020, after a decennial growth rate of approximately one hundred percent, the 77 postgraduate programs in Geography were distributed among the 27 Federal Units, and in São Paulo, the state yet with the highest number, we found about 10% of the total amount. It was also found that, different from what is suggested by the absolute numbers and by some authors, when confronted with the demographic dimension of the region, since the early years of the present century, the Southeast is characterized by a deficiency in the number of the postgraduate programs in Geography, a characteristic shared with the Northeast Region, while the others show a surplus, notably the Center-West, a region that has been the relatively most benefited by the recent expansionist policy.